A molecular dynamics based cohesive zone model for interface failure under monotonic tension of 3D four direction SiCf/SiC composites. (15th October 2021) - Wang, Rongqiao; Han, Jiangbo; Mao, Jianxing; Hu, Dianyin; Liu, Xi; Guo, Xiaojun
Highlights: Molecular dynamics simulation is performed for SiC/PyC interface damage. Cohesive zone model is established to bridge microscale to mesoscale. Representative volume element is constructed for 3D braided CMC. Model validation is realized by monotonic tension experiment. Abstract: Aiming at a mechanics-based prediction on the progressive damage in SiC fiber reinforced SiC matrix (SiCf /SiC) composites, multiscale simulation coupling molecular dynamics (MD) and finite element method (FEM) is established with specific concern on the silicon carbide/pyrocarbon (SiC/PyC) interface separation behavior. The MD simulation is employed to evaluate the interface damage with preset crack. Interfacial mechanical response at microscale between SiC and PyC under pure normal and tangential stresses is captured. Accordingly, a cohesive zone model (CZM) for the SiC/PyC interface separation is established, generalized to mixed loading conditions and validated by FEM fiber push-out simulation. Integrating proposed CZM to FEM to construct 3D four direction SiCf /SiC composites, the multiscale damage model is eventually consistent with the data from monotonic tension test. This research provides new physical insights on SiC/PyC interface damage under complex stress state, and contributes to a promising tool for mechanical performance prediction on 3D four direction SiCf /SiC composites.